Capacity loss estimation for li-ion batteries based on a semi-empirical model - Rabah Mohammed; Immonen Eero; Shahsavari Sajad; Haghbayan Mohammad-Hashem; Murashko Kirill; Immonen Paula (United Kingdom, 2022)
Understanding battery capacity degradation is instrumental for designing modern electric vehicles. In this paper, a Semi-Empirical Model for predicting the Capacity Loss of Lithium-ion batteries during Cycling and Calendar Aging is developed. In order to redict the Capacity Loss with a high accuracy, battery operation data from different test conditions and different Lithium-ion batteries chemistries were obtained from literature for parameter optimization (fitting). The obtained models were then compared to experimental data for validation. Our results show that the average error between the estimated Capacity Loss and measured Capacity Loss is less than 1.5% during Cycling Aging, and less than 2% during Calendar Aging. An electric mining dumper, with simulated duty cycle data, is considered as an application example.
Proceedings of the 35th ECMS International Conference on Modelling and Simulation ECMS 2021